PENERAPAN MEDIA WAYANG KARTUN TERHADAP KETERAMPILAN MENYIMAK di SD ISLAM PADANG - Frasandy, Rendy Nugraha; Rahmatika, Ulva; Rahmawati, Dwi Nur Umi; Dorisno, Dorisno (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2023)
TThis research was motivated by students who were less interested in learning to listen to stories so that it had an impact on the learning outcomes of Indonesian students in grade V, of which there were 60 students, 35 students or 58.33% were under the Minimum Mastery Criteria (KKM). ) determined by the school 75. The aim in writing this thesis is to find out the effect of using wayang cartoon media on listening skills in Indonesian subjects. This type of research is quasi-experimental (Quasi-Experimental) with a non-equValent control group design. The population in this study are students of class V. Taking a sample of 20 experimental class students and 20 control class students. Data collection techniques were carried out by tests, observations and documentation. Data analysis techniques were carried out by normality test, homogeneity test, and hypothesis testing using SPSS 26. The results of the study showed that the use of wayang cartoon media had an effect on story listening skills in fourth grade students of SD Islam Padang. This can be seen from the comparison of the pretest and posttest mean values of the experimental and control classes. The pretest average obtained by the experimental class was 66.25 while the pretest average obtained by the control class was 69.50. After taking action on both classes, the posttest average for the experimental class was 79.50, while the posttest average for the control class was 75.75. From the t-test calculation with a significance level of 0.05, tcount (32.910) > ttable (2.22691) and sig value (0.000) t table or sig.